2006
DOI: 10.1002/pola.21538
|View full text |Cite
|
Sign up to set email alerts
|

Novel organosoluble polynorbornene bearing a polar, pendant, ester‐bridged epoxy group via living ring‐opening metathesis polymerization

Abstract: A novel organosoluble polynorbornene bearing a polar, pendant, ester‐bridged epoxy group [poly(oxiran‐2‐ylmethyl 2‐methylbicyclo[2.2.1]hept‐5‐ene‐2‐carboxylate) (polyOMMC)] was prepared via the living ring‐opening metathesis polymerization (ROMP) of active norbornenes with a Ru catalyst. PolyOMMC exhibited excellent solubility in a variety of solvents. The number‐average molecular weight of polyOMMC linearly increased with the [M]/[I] ratio (where [M] is the monomer concentration and [I] is the initiator conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…Monomer 2 showed characteristic peak of epoxy at 912 cm −1 , and the peak at 1725 cm −1 was attributed to CO of the ester group . The isomers of endo and exo were calculated by NMR based on 1.8 ∼ 2.4 ppm (monomer 1 ) and 6.1–6.3 ppm (monomer 2 ) respectively . It was found that the endo/exo ratio of monomer 1 was 1/1 and 2/1 for monomer 2 , which were consistent with the findings in references very well …”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Monomer 2 showed characteristic peak of epoxy at 912 cm −1 , and the peak at 1725 cm −1 was attributed to CO of the ester group . The isomers of endo and exo were calculated by NMR based on 1.8 ∼ 2.4 ppm (monomer 1 ) and 6.1–6.3 ppm (monomer 2 ) respectively . It was found that the endo/exo ratio of monomer 1 was 1/1 and 2/1 for monomer 2 , which were consistent with the findings in references very well …”
Section: Resultssupporting
confidence: 87%
“…(28)], especially when flexibility is tuned by adjusting the chemical structures of macromolecular backbones. Besides, an epoxy‐containing norbornene monomer with rising potentials as a new crosslinker in resin industry was also used in this study . A second aim of this contribution is to test the flame retardance and photo resistance of PCPs for the promising industrial applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is due in part to their relative ease of handling/storage as well as their high functional group tolerance. Indeed, a wide range of monomers bearing a broad spectrum of functionality have been successfully polymerized via ROMP employing Grubbs' catalyst 8–17. However, Grubbs' catalyst is not tolerant of all functionality.…”
Section: Introductionmentioning
confidence: 99%
“…Interest in polymers of cyclic olefins such as bicyclo[2.2.1]hept‐2‐ene(norbornene) and its derivatives has increased dramatically over the past decade. Norbornene (NBE) and its derivatives are commonly polymerized via four well‐known polymerization mechanisms with various transition‐metal‐containing catalysts: cationic polymerization,1 radical polymerization,2 ring‐opening metathesis polymerization (ROMP),3–15 and vinyl‐addition polymerization 16–22. Among them, vinylic polymerization has drawn more attention because it yields a special polynorbornene (PNBE) with a 2,3‐connected structure, which contains intact bicyclic units and is rotationally strongly constrained 23–25.…”
Section: Introductionmentioning
confidence: 99%